Factors Associated with Lower Urinary Tract Symptoms in Thai Women with Uterine Leiomyomas - Suchada Erjongmanee; Suvit Bunyavejchevin (The Royal Thai College of Obstetricians and Gynaecologists, 2019)
Objectives: To identify the associated factors between uterine leiomyoma and lower urinary tract symptoms (LUTS) in Thai women. Materials and Methods: One hundred and thirty eightwomen presenting with uterine leiomyoma at gynecologic out-patients clinic, King Chulalongkorn Memorial Hospital during August, 2014-March, 2015 were included. International Consultation on Incontinence Questionnaire- Female Lower Urinary Tract Symptoms Module (ICIQ-FLUTS) questionnaires were completed by all patients to identify the presence of LUTS. The LUTS case was defined by the present of any ICIQ-FLUTS questions score more than or equal to 2. The case: control ratio was 1:1. The controls were matched at the same day or within 3 days of the case. The patients' characteristics and the ultrasonographic data were collected. Results: Among 138 leiomyoma patients were participated (69 cases and 69 controls). The mean age was 43.52 ± 7.4 and 44.86 ± 7.4 years respectively. There was no difference in body mass index and menopausal status. By univariate comparison, the mean of the total uterine volume and the largest leiomyoma volume were significantly different between groups. After the multivariate analysis, only the uterine volume more than 400 cm3 (odds ratio (95% confidence interval) = 2.44 (1.03-5.75)) and the largest leiomyoma volume more than 14 cm3 (odds ratio (95% confidence interval) = 2.53 (1.02-6.37)) were significantly associated with LUTS. Conclusion: Uterine volume ≥ 400 cm3 and largest leiomyoma volume ≥ 14 cm3 were the risk factors of LUTS in Thai women with leiomyoma.